2002
DOI: 10.1007/s00125-002-0845-2
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of Type I diabetes has not increased but shifted to a younger age at diagnosis in the 0–34 years group in Sweden 1983 to 1998

Abstract: Aims/hypothesis. To analyse the incidence of Type I (insulin-dependent) diabetes mellitus in the 0-34 years age group in Sweden 1983-1998. Methods. Incidence and cumulative incidence per 100 000 and Poisson regression analysis of age-period effects was carried out using 11 751 cases from two nation-wide prospective registers. Results. Incidence (95%-CI) was 21.4 (20.8-21.9) in men and 17.1 (16.6-17.5) in women between 0 and 34 years of age. In boys aged 0-14 and girls aged 0-12 years the incidence increased ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
139
3
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(158 citation statements)
references
References 38 publications
14
139
3
1
Order By: Relevance
“…In Sweden, a nationwide prospective register found no increase in young adults aged 15-34 years, and analysis of cumulative rates indicated a shift towards a younger age of onset rather than an overall rise in type 1 diabetes, at least up to the age of 35 [4]. Similar results were reported from Belgium [5].…”
Section: Introductionsupporting
confidence: 63%
“…In Sweden, a nationwide prospective register found no increase in young adults aged 15-34 years, and analysis of cumulative rates indicated a shift towards a younger age of onset rather than an overall rise in type 1 diabetes, at least up to the age of 35 [4]. Similar results were reported from Belgium [5].…”
Section: Introductionsupporting
confidence: 63%
“…A shift to an early onset of type 1 diabetes, rather than a true increase in the incidence of the disease, can be seen [24,25]. Only 7.5% of our patients were in the 15-20-years age category, which may be the result of lower incidence rates or incomplete retrieval [26].…”
Section: Discussionmentioning
confidence: 66%
“…Birthweight [5], as well as the prevalence of overweight children [7], has gradually increased in Sweden over recent decades. This trend seems to parallel the increasing incidence of type 1 diabetes occurring in childhood, especially in the younger age-at-onset groups, but is not seen in age groups older than 15 years at diagnosis [7].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in overall growth of children as reflected by increments in height and weight would accelerate an already ongoing autoimmune destruction of beta cells by increasing the need for insulin [6]. Interestingly it has been shown that the incidence of type 1 diabetes is not increasing, but rather decreasing among young adults in Sweden [7]. Therefore the changing incidence over time would reflect an earlier onset rather than a total increase in occurrence of the disease at least up to the age of 35 years.…”
Section: Introductionmentioning
confidence: 99%